Religion in the Achaemenid Persian Empire: Emerging Judaisms and Trends - Edelman, Diana; Fitzpatrick-McKinley, Anne; Guillaume, Philippe (Orientalische Religionen in der Antike, 2019)
Lange Zeit meinte man, dass die Herrscher des Achämenidenreichs eine Politik der religiösen Toleranz innerhalb ihrer weitläufigen Provinzen und in ihren Kolonien vertraten. Die vierzehn Beiträge dieses Sammelbandes untersuchen verschiedene Aspekte der dynamischen Interaktion zwischen kaiserlichen und kommunalen Ebenen, die hauptsächlich auf regionale religiöse Praktiken Einfluss hatten. Einige der Beiträge befassen sich mit den aufkommenden Formen des Judentums unter achämenidischer Vorherrschaft, andere mit achämenidischer Religion, königlicher Ideologie und politischer Taktik bezüglich der Religion. Manche behandeln Aspekte der phönizischen Religion und dem Wandel hin zu ägyptischen religiösen Bräuchen. Ein weiterer Beitrag spricht die Ausübung verschiedener Religionen in Phrygien an, auf die Abbildungen auf Siegeln hinweisen. Gemeinsam zeigen die Beiträge, dass Toleranz mehr Teil politischer Zweckmäßigkeit war als eine allgemeingültige Strategie, die aus religiöser Überzeugung entstanden war.Inhaltsübersicht Part I: Trends in Emerging Judaisms James Anderson: Creating Dialectical Tensions: Religious Developments in Persian-Period Yehud Reflected in Biblical Texts – Philip R. Davies: Monotheism, Empire, and the Cult(s) of Yehud in the Persian Period – Russell Hobson, Were Persian Period 'Israelites' Bound by Ethnicity or Religious Affiliation? The Case of the Southern Transjordan – Philippe Guillaume: Non-violent Re-readings of Israel's Foundational Traditions in the Persian Period (the Calendar System in P) – Lowell Handy: Josiah as Religious Peg for Persian Period Jews and Judaism – Christian Frevel / Katharina Pyschny: A Religious Revolution Devoursits Children. The Iconography of the Persian Period Cuboid Incense Burners Part II: Other Religious Trends in the Persian Anne Fitzpatrick-McKinley: Continuity between Assyrian and Persian Policies Toward the Cults of their Subjects – Jason M. Silverman: Was There an Achaemenid 'Theology' of Kingship? The Intersections of Mythology, Religion, and Imperial Religious Policy – Yannick Muller: Religion, Empire and Mutilation: A Cross-Religious Perspective on Achaemenid Mutilation Practices – Diana Edelman: Iconography on Double-Shekel Sidonian Coinage in the Persian Period: Is It a God or a King in the Chariot? – Mark Christian: Whose Rites and Whose Wrongs? Religious Contributions of Contingents within the Persian Navy – Damien Agut-Labordère: Political Piety-for-Predation Policy: Persian and Egyptian Gods during the Achaemenid Period – Jared Krebsbach: Achaemenid Persian Patronage of Egyptian Cults and Religious Institutions in the Twenty-seventh Dynasty: A Study of Political Acumen in the Ancient World – Deniz Kaptan: Religious Practices and Seal Imagery in Achaemenid Hellespontine Phryia